Heterooxide Composites for Photocatalytic Disintegration of Toxicants: Synthesis and Application - Sakhnenko, M. D.; Karakurkchi, H. V.; Korohodska, Alla Mykolaivna; Yermolenko, I. Yu.; Maiba, M. V.; Indykov, S. M. (BoScience Publisher, 2022)
The processes of plasma electrolyte formation of heteroxide coatings on titanium alloys as photocatalytic materials for the decomposition of natural and man-made toxicants have been studied. The coatings were synthesized from aqueous solutions of diphosphate with the addition of dopant metal salts. The surface of TiO2 coating is characterized by toroidal mesostructures, and multicomponent compositions have a more developed surface, which has a positive effect on their functional properties, as well as subsequent heat treatment. The photocatalytic properties of the coatings were tested in a model oxidation reaction of the methyl orange azo dye. Among the studied coatings TiO2∙ZnO is the most catalytically active one.
Keywords: plasma-electrolytic oxidation; titanium alloys; photocatalyst; heteroxide coatings; surface morphology